ILMU AMTSAL AL-QUR’AN - Abdul Khair; M. Rifky Juliansyah; Nurul Hidayah; Sri Juwita; Akhmad Dasuki (PT. Hasba Edukasi Mandiri, 2025)
The process of delivering information in teaching and learning becomes more engaging, effective, and efficient when expressed through beautiful and meaningful language. One of the strategies to achieve this is by using amtsal (parables). Amtsal in the Qur’an function as abstract visualizations conveyed through various forms of expression by analogizing one thing to another that is similar or comparable. An amtsal is an expression intended to resemble a situation described in a statement with the condition in which the statement is presented. It is used to demonstrate the quality of an outcome, clarify fundamental and abstract matters, and provide beneficial lessons for its audience. Its purpose is to convey truth and highlight the significance of the message it contains. In educational practice, the use of amtsal as a medium aims to build certain premises so that learners can formulate logical inferences (istinbāṭ) based on them.